The effectiveness of maternity waiting homes in reducing perinatal mortality: a case–control study in Ethiopia. Issue 4 (16th April 2021) - Dalla Zuanna, Teresa; Fonzo, Marco; Sperotto, Milena; Resti, Carlo; Tsegaye, Ademe; Azzimonti, Gaetano; Manenti, Fabio; Putoto, Giovanni; Bertoncello, Chiara
Abstract : Background: The 2030 Agenda for Sustainable Development aims to reduce neonatal mortality to at least 12 per 1000 live births. Most of the causes can be prevented or cured. Access to quality healthcare during pregnancy and labour is the key to reduce perinatal deaths, and maternity waiting homes (MWHs) may have an impact, especially for women who live far from the healthcare system. We conducted a case–control study to evaluate the effectiveness of MWH in reducing perinatal mortality in a secondary hospital in Ethiopia. Methods: We did a nested case–control study from January 2014 through December 2017. The enrolled cases were mothers whose childbirth resulted in stillbirth or early neonatal death. The controls were mothers with an alive baby at 7 days or with an alive baby on discharge. We collected demographic, anamnestic, pregnancy-related and obstetric-related data. The effectiveness of the MWH on perinatal death was assessed by a logistic regression model, adjusted for all other variables investigated as potential confounders. We also did a sensitivity analysis to explore the role of twin pregnancies. Results: We included 1175 cases and 2350 controls. The crude analysis showed a protective effect of the MWH towards perinatal mortality (OR=0.700; 95% CI: 0.505 to 0.972), even more protective after adjustment for confounders (adjusted OR (AOR)=0.452; 95% CI: 0.293 to 0.698). Sensitivity analyses showed a consistent result, even excluding twin pregnancies (AOR=0.550; 95% CI: 0.330 to 0.917). Conclusion: MWHs appear to reduce perinatal mortality by 55%. Our findings support the decision to invest in MWH to support pregnant women with higher quality and more comprehensive healthcare strategy, including quality antenatal care in peripheral primary care clinics, where risk factors can be recognised and women can be addressed for admission to MWH.